DIVIDEN, HUTANG, DAN KEPEMILIKAN INSTITUSIONAL DI PASAR MODAL INDONESIA: PENGUJIAN TEORI KEAGENAN - Teguh Prasetyo (Jurnal Dinamika Manajemen)
This study aims to test theagency theory in Indonesian capital market wasproxiedbythe theagency conflicts controlling mechanism which are dividends, debtand institution alownership.The data is pooled data with the observation period from the year 2004-2010. The method of analysis used in this study is multiple regression analysis, and Two-Stages Least Square (2SLS). The results showthe dividend has a positive effect on performance an debt has negative effect. More over, institution alownership has a positive effect on performance. Meanwhile, Simultaneously relationship between the three models are not significant. However, the relationship between dividends and debt significant. It means that dividends can replace debt andvice versato control the agency conflict.